Suberites spermatozoon ... - Morozov, Grigori; Strelkova, Natalya Anisimova; Zimina, Olga; Sabirov, Rushan (Zenodo, 2023)
Suberites spermatozoon (Schmidt 1875) (Fig. 4a–h) Cometella spermatozoon: Schmidt 1875, p. 116; Pl. 1, fig. 2; Thiele 1903, p. 378, fig. 4. Suberites spermatozoon: Fristedt 1885, pp. 18–19; Pl. 2, figs. 4a–e; Fristedt 1887, pp. 429–430. Ficulina spermatozoon: Rezvoi 1928, pp. 82–85, figs. 6–7; Hentschel 1929, pp. 871–872; Burton 1930, p. 496. Suberites lütkenii var. spermatozoon: Arndt1935, p. 41, fig. 65. Choanites spermatozoon: Alander 1942, p.79. Suberites domuncula var. spermatozoon: Koltun 1966, p. 96, fig. 68, Pl. 31, figs. 1–9. Material analyzed. Kara Sea, PINRO trawl survey, Pomor, 1994, st. 3 (72.417N, 59.4378E), depth 157 m (1 specimen). Boris Petrov, 2000, st. 29 (76.9362N, 85.7631E), depth 71 m, temperature -0.3 °C, salinity 34.3 psu (1 specimen); st. 30 (75.9864N, 83.361E), depth 57 m, temperature 0.2 °C, salinity 33.9 psu (2 specimen). Barents Sea, PINRO trawl survey, Muklevich, 2003, st. 34 (72.0385N, 33.3903E)), depth 265 m, temperature 2.66 °C, salinity 34.959 psu (7 specimens, ... : Published as part of Morozov, Grigori, Strelkova, Natalya Anisimova, Zimina, Olga & Sabirov, Rushan, 2023, A preliminary account of the Arctic / Subarctic Suberites (Porifera: Demospongiae) fauna, pp. 50-70 in Zootaxa 5357 (1) on pages 58-60, DOI: 10.11646/zootaxa.5357.1.2, http://zenodo.org/record/10012504 ...